Corrigendum to “The relationship between critical thinking and problem-solving skills in social studies among primary school students.” - Uus Kuswendi; Bunyamin Maftuh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
In the original published version of this article, the authors inadvertently omitted “Universitas Pendidikan Indonesia, Bandung, Indonesia” as the second affiliation for Uus Kuswendi. The affiliation of Uus Kuswendi has now been corrected to include both Institut Keguruan dan Ilmu Pendidikan Siliwangi, Cimahi, Indonesia, and Universitas Pendidikan Indonesia, Bandung, Indonesia. The authors apologize for the error. The PDF version of the article has been updated to correct the error.